Experimental investigation of semiactive robust control for structures with magnetorheological dampers - Aggumus, Huseyin; Cetin, Saban (SAGE PUBLICATIONS LTD, 2018)
This study investigates reducing the vibration of structures under different earthquakes using magnetorheological dampers. To investigate the effect of the magnetorheological damper arrangement on reducing the vibration amplitude of structures, experimental studies are conducted in which magnetorheological dampers are commanded by a robust controller. So, the performance of the system is investigated using different combinations of two magnetorheological dampers on a building and three different arrangements for dampers are considered for experimental study. Additionally, an H infinity controller is designed to determine the voltage transmitted to the magnetorheological dampers. The results show that the magnetorheological damper commanded with the robust controller effectively reduces the vibration of a six-story steel structure. Furthermore, the magnetorheological damper arrangement in which the one end is connected to the ground reduces the vibration amplitudes.
Keywords: Structural control; magnetorheological damper; magnetorheological damper layout; H-infinity robust control; shaking table test; NONLINEAR CONTROL; CONTROL-SYSTEM; SEISMIC ALLEVIATION; CONTROL STRATEGIES; MR DAMPERS; SUPPRESSION; MODEL; SUSPENSION; Acoustics